Perspectives from parents and clinicians on an ecology-focused approach to a group well-child care - Ishaan T. Shah; Nina D. Ham; Hassan Lubega; Christopher L. Boswell; Esther Kim Liu; Renée D. Boynton-Jarrett (BMC Primary Care)
Abstract Background Group well-child care (GWCC) is a novel group-based alternative for pediatric primary care visits that may allow for adaptations that better tailor to the needs of underserved populations. This qualitative study investigates clinician and parent perspectives on the acceptability and feasibility of integrating ecology-focused content in GWCC using semi-structured interviews with GWCC parent-graduates and ecology-focused child clinicians. Methods Ecology-focused child clinicians were purposively sampled via email outreach. GWCC parent graduates were recruited via announcement in private Facebook groups. One-on-one interviews were conducted via videoconference, transcribed, and analyzed using an inductive approach. Parent and clinician thematic analyses were independently conducted to construct shared domains. Results Nine GWCC parent-graduates and nine ecology-focused child clinicians were recruited into the study. Four overarching themes were constructed across parent and clinician responses: questions about clinical appropriateness, parent and clinician desires for educational support, influences of perceptions of nature on clinicians, and parent desires to develop independence and autonomy. Conclusion This study identified nuanced considerations from the perspective of parents and clinicians for the implementation of ecology-focused content in the GWCC setting. Understanding the range of preferences parents and clinicians may have over ecology-focused content can help GWCC clinicians in designing ecology-focused preventive counseling materials.